2002
DOI: 10.1053/jhep.2002.31024
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination for hepatitis B after transplantation: A realistic goal?

Abstract: L iver transplantation for hepatitis B has become remarkably successful over the past decade. This success has been predicated upon effective therapy to prevent clinical infection of the transplanted liver by hepatitis B virus (HBV). The cornerstone of therapy to prevent HBV infection in the transplanted liver has been the use of hepatitis B immune globulin (HBIG). With the availability of effective antiviral therapy (especially lamivudine with others soon to be available), the repertoire for HBV containment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…On the other hand, one of our recent nonresponders vaccinated while receiving lamivudine, developed positive serum hepatitis B surface antigen and HBV DNA 9 months after the failure of vaccination despite the uninterrupted administration of oral lamivudine. Although we currently have no data regarding lamivudine resistance in this patient, the case appears to be similar to the one described by Pruett 3 and suggests that, at least in nonresponders to HBV vaccination, hepatitis B immune globulin may be a safer prophylactic regimen than lamivudine.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…On the other hand, one of our recent nonresponders vaccinated while receiving lamivudine, developed positive serum hepatitis B surface antigen and HBV DNA 9 months after the failure of vaccination despite the uninterrupted administration of oral lamivudine. Although we currently have no data regarding lamivudine resistance in this patient, the case appears to be similar to the one described by Pruett 3 and suggests that, at least in nonresponders to HBV vaccination, hepatitis B immune globulin may be a safer prophylactic regimen than lamivudine.…”
supporting
confidence: 78%
“…Traditionally, the threshold for considering a therapy cost effective has been $50,000 per life year saved or quality adjusted life year saved. 3 Since no incremental increase in life expectancy was demonstrated and quality of life measures were the same in both groups, whether the additional costs of TIPS are justified for the purported benefits is a subjective one. Consideration should be based on the availability of local resources and competing therapies that may deliver health care at a more cost-effective rate.…”
Section: Is Tips a Cost-effective Therapy For The Prevention Of Varicmentioning
confidence: 99%
“…The rationale for combining vaccine with HBIg in phase I is supported by the hypothesis that the formation of HBIg/HBsAg complexes might increase vaccine immunogenicity [44,45]. The need to continue vaccination after HBIg withdrawal in phase II was considered to be crucial to strengthen the response to vaccination and to exclude the possibility of detecting spurious anti‐HBs titers.…”
Section: Discussionmentioning
confidence: 99%
“…The Barcelona group [65] published a favourable study for this approach. However, since these initial report new studies indicated that this intriguing concept might be not as easy as originally thought to bring into the clinic [66,67]. Especially the study by Angelico et al [66] suggested that there is a strong variation in the immune response after HBsAg vaccination in patients after liver transplantation.…”
Section: Strategies To Lower the Cost Of Hbv-reinfection Prophylaxismentioning
confidence: 99%